Efficacy and Affecting Factors of 131I Thyroid Remnant Ablation After Surgical Treatment of Differentiated Thyroid Carcinoma - Wang, Chen; Diao, Hongcui; Ren, Ping; Wang, Xufu; Wang, Yangang; Zhao, Wenjuan (Frontiers in Oncology, 2018)
Purpose: Radioiodine (131I) thyroid remnant ablation is an important treatment of differentiated thyroid carcinoma (DTC) and various factors affecting its efficacy have been reported but not well defined. The aim of our study was to evaluate the efficacy and the affecting factors of 131I ablation after total or near-total thyroidectomy in a relative large DTC cohort. Methods: 261 DTC patients with negative thyroglobulin antibody received 100-200 mCi 131I for thyroid remnant ablation after total or near-total thyroidectomy between January 2012 and October 2015 in our hospital. The efficacy and affecting factors of 131I ablation therapy were retrospectively investigated. Results: The success rate of the first 131I thyroid remnant ablation was 65.90%. Univariate analysis demonstrated that larger tumor size, higher level of pre-ablation stimulated thyroglobulin (sTg), intermediate to high risk stratification for recurrence, and lymph node and distant metastases were associated with a lower success rate of the first 131I ablation (all p＜0.05). Multivariate logistic regression analysis showed that tumor size, pre-ablation sTg, and lymph node and distant metastases were independent factors affecting the efficacy of the first 131I ablation. Areas under receiver operating characteristic curves for sTg, sTg/TSH ratio, and tumor size to predict unsuccessful ablation were 0.831, 0.824 and 0.648, respectively. The threshold values were 4.595 ng/ml, 0.046 mg/IU, and 1.350 cm, respectively. The sensitivities were 95.51%, 96.63% and 73.03% and the specificities were 64.54%, 61.63% and 49.41%, respectively. The excellent response (ER) ratio of the successful group was significantly higher than that of the unsuccessful group. Conclusions: The efficacy of the first 131I thyroid remnant ablation after surgical treatment of DTC is well demonstrated, and tumor size, pre-ablation sTg, lymph node and distant metastases are independent factors affecting its efficacy.